PERLINDUNGAN INDIKASI GEOGRAFIS PADA PRODUK LOKAL DALAM SISTEM PERDAGANGAN INTERNASIONAL - Hendra Djaja (University of Merdeka Malang, 2013)
The global concept of intellectual wealth right protection today did not only give protection toward product ofinnovation or technology invention, but also widen the substance on various products which were reallynatural resource so the exclusiveness attached in the product could also show the origin and the characteristicor special character. This kind of product was a commodity which had reputation with high economy valuelocally, nationally and even internationally. In free market era today, protection concept of HKI - TRIPs hadagreed or dealt to give law protection of geographical indication toward goods or processed product producedby society, as it was written in regulation No 15 year 2001 about trade mark and government regulation No 51year 2007 about geographical indication.